The impact of the (Namous) model on cognitive achievement and learning basic attack skills in foil fencing for students - كاظم, م.م. تغريد مهدي; منير, م.م. شهد; الطائي, أ.د. ظافر (Sulaimani Journal for Humanities, 2026)
To investigate the impact of the NAMOUS model on learning basic attack fencing skills, researchers used an experimental approach with a sample of third-year students at the College of Physical Education and Sports Sciences, University of Diyala. After completing the research procedures, including identifying basic attack skills, conducting pre- and post-tests, and collecting and processing the data, the researchers concluded the following: The use of the NAMOUS model has a positive impact on cognitive achievement and learning basic attack fencing skills with the foil among the research sample. The experimental group outperformed the control group in learning. At the same time, the method used by the instructor with the control group had an impact on their learning, as evidenced by the post-test results. The researchers recommend the following: the necessity of changing and diversifying teaching methods to make the process of learning and performing basic attack skills more engaging and exciting for students; and conducting similar studies using the NAMOUS model on physical, motor, and mental variables, as well as on the performance of other basic movements and skills in fencing, to determine its impact on these aspects
Keywords: (Namus) model; basic attack skills; foil fencing; students